2013
DOI: 10.1016/j.ijbiomac.2012.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Urea-induced unfolding of Glossoscolex paulistus hemoglobin, in oxy- and cyanomet-forms: A dissociation model

Abstract: The urea effect on the giant extracellular hemoglobin of Glossoscolex paulistus (HbGp) stability was studied by analytical ultracentrifugation (AUC) and small angle X-ray scattering (SAXS). AUC data show that the sedimentation coefficient distributions curves c (S), at 1.0 mol/L of urea, display a single peak at 57 S, associated to the undissociated protein. The increase in urea concentration, up to 4.0 mol/L, induces the appearance of smaller species, due to oligomeric dissociation. The sedimentation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
5
0
1
Order By: Relevance
“…4). Recent studies of characterization of HbGp subunits by SEC and SDS-PAGE suggest that this peak corresponds to the same band of the pure native HbGp [9]. The elution volumes of the other species, as well as, previous analytical ultracentrifugation and MALDI-TOF-MS studies [29,46], imply that the peaks II, III and IV are due to the contributions of the dodecamer (abcd) 3 , trimer abc and monomer d, respectively (see Scheme 2 of the HbGp oligomeric structure and its subunits).…”
Section: Importance Of Intrinsic Metals In the Hbgp Oligomeric Stabilitymentioning
confidence: 90%
See 3 more Smart Citations
“…4). Recent studies of characterization of HbGp subunits by SEC and SDS-PAGE suggest that this peak corresponds to the same band of the pure native HbGp [9]. The elution volumes of the other species, as well as, previous analytical ultracentrifugation and MALDI-TOF-MS studies [29,46], imply that the peaks II, III and IV are due to the contributions of the dodecamer (abcd) 3 , trimer abc and monomer d, respectively (see Scheme 2 of the HbGp oligomeric structure and its subunits).…”
Section: Importance Of Intrinsic Metals In the Hbgp Oligomeric Stabilitymentioning
confidence: 90%
“…The increase of polydispersity index in this temperature range between 40 and 47°C indicates the existence of and equilibrium of different HbGp subunits in the solution. Previous studies on the stability of HbGp under denaturing conditions, such as, alkaline pH, have shown that the hemoglobin undergoes oligomeric dissociation into smaller species, such as, dodecamer (abcd) 3 , tetramer abcd, trimer abc and monomer d [9]. These species are characterized by hydrodynamic diameters (D H ) values of 5.1 nm for the monomer d, 7-12 nm for the mixture of trimer abc and a linker subunit, and 10-14 nm for the dodecamer (abcd) 3 [9,46].…”
Section: Importance Of Intrinsic Metals In the Hbgp Oligomeric Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…15B). (Fig.15F), e o perfil da curva é consistente com a presença de subunidades dissociada em solução [19,33,58,59]. …”
Section: Cianometa-hbgpunclassified